Anomalous breaking of scale invariance in a two-dimensional fermi gas - Holten, Marvin; Bayha, Luca; Klein, Antonia Clara; Murthy, Puneet A.; Preiss, Philipp; Jochim, Selim (Physical review letters, 2018)
The frequency of the breathing mode of a two-dimensional Fermi gas with zero-range interactions in a harmonic confinement is fixed by the scale invariance of the Hamiltonian. Scale invariance is broken in the quantized theory by introducing the two-dimensional scattering length as a regulator. This is an example of a quantum anomaly in the field of ultracold atoms and leads to a shift of the frequency of the collective breathing mode of the cloud. In this work, we study this anomalous frequency shift for a two-component Fermi gas in the strongly interacting regime. We measure significant upwards shifts away from the scale-invariant result that show a strong interaction dependence. This observation implies that scale invariance is broken anomalously in the strongly interacting two-dimensional Fermi gas.
Gesehen am 19.11.2019